Peran Guru Pendididkan Agama Islam dalam Membentuk Karakter Peserta Didik SMP Genetasi Z di Era Digital Melalui Pemanfaatan Media Sosial, Kurikulum Berbasis Cinta, dan Pendekatan: The Role of Islamic Religious Education Teachers in Shaping the Character of Generation Z Junior High School Students in the Digital Era Through the Utilization of Social Media, Love-Based Curriculum, and Approaches - Dwi Januarti; Hatiti; Khofifiah Adawiyah Khairani; Rahayu; Muji Agus Sofyandi (Pendidikan Al-Gafari, 2026)
The rapid development of information and communication technology has significantly impacted the lives of students, especially Generation Z, who grew up with widespread internet and social media access. This study aims to analyze the role of Islamic Religious Education teachers in shaping the character of Generation Z junior high school students in the digital era and identify strategies used to address these challenges. This study used a qualitative approach with field research. Data were collected through in-depth interviews, observation, and documentation with Islamic Religious Education teachers as key informants. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing, while data validity was tested using triangulation techniques. The results show that Islamic Religious Education teachers play a crucial role as educators, mentors, role models, motivators, and facilitators in shaping students' character. The strategies implemented include fostering religious activities, utilizing social media as a means of digital da'wah, using creative and interactive learning methods, implementing a love-based curriculum, and engaging in a personal approach through counseling.